Medication Causes and Treatment of Delirium in Patients With and Without Dementia - Anita Elaine Weidmann; Rut Matthíasdóttir; Guðný Björk Proppé; Ivana Tadić; Pétur Sigurdur Gunnarsson; Freyja Jónsdóttir (Brain and Behavior)
ABSTRACT Introduction Medication associated with delirium in adult patients is poorly understood and considered both a predisposing and precipitating factor. Prescribing advice is lacking. This systematic review aims to collate evidence on medication risks in delirium associated with causation and treatment including mechanisms, treatment, and treatment alternatives in adult patients with and without dementia in an attempt to support prescribing decision‐making and patient safety in healthcare practice. Methods A literature review of CNIAHL, IPA, APA PsycArticles, PubMed, Cochrane Library, SAGE Education, Science Direct, SCOPUS, Web of Science Core Collection, National Grey Literature Collection, Google Scholar, Ovid, and Open Access Theses and Dissertations was performed from 2000 for articles published in English. Original, peer‐reviewed studies, meta‐analyses, systematic and narrative reviews, case reports, commentaries, editorials, and scientific communication focusing on medication‐associated delirium risk in adult patients (≥ 18 years) were included. Title, abstract, and full‐text screening were completed independently by two reviewers. CASP, MMAT, JBI, and the SANAR tool were used to assess reporting quality. The protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO) (ID: CRD42022366020). Results Out of 3867 papers identified, 106 were included. Information about 20 different drug classes was reported. Despite a respectable quality rating, medication detail provided often lacks specificity about mechanisms of action, individual risk, dosage instructions, symptoms, and avoidable drug–drug combinations. Details on underlying mechanisms, pharmacological treatment, combinations, therapeutic alternatives, and medication associated with delirium in dementia patients were extracted. Conclusions This summary offers the most detailed summary of medication‐related information for delirium in patients with and without dementia to support prescribing decisions. While the detailed results can be used to support a multicomponent approach to delirium care, they also support the call for categorizing delirium into distinct etiological subgroups. The effect of medication on gut microbiome diversity and composition should be considered.